2018
DOI: 10.1051/e3sconf/20184400032
|View full text |Cite
|
Sign up to set email alerts
|

Termomodernization analyses of terraces located above existing apartments

Abstract: The paper discusses the principles of terraces design assessment with different types of insulation. It presents and compares layer systems and choice of materials in the existing terraces and modernized. Special attention was paid to the need to ensure adequate thermal insulation in areas adjacent to the balconies and terraces as well as terraces. See also the main principles of good design such structures, taking into account issues of temperature and humidity, as well as making the modernization of the terr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Studies carried out by [14] in Ottawa, Canada, showed that following 22 months of observation, the median temperature fluctuations in an uncovered roof membrane were 42-47 • C, whereas a green roof reduced temperature fluctuations in the roof membrane to a median of 5-7 • C the entire year. In addition to thermal aspects, there are many other arguments supporting the application of green roofs, terraces and walls on a large scale in urban areas: they counteract climate changes and reduce the emission of CO 2 into the atmosphere, nullify the negative effects of urbanization, reduce smog [15][16][17], retain rainwater and delay runoff [18][19][20][21], suppress noise, create friendly living and leisure space, and improve the aesthetics of buildings [22,23]. In Poland, work is currently in progress on preparing urban adaptation plans for climate change in which green roofs are among the basic adaptation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out by [14] in Ottawa, Canada, showed that following 22 months of observation, the median temperature fluctuations in an uncovered roof membrane were 42-47 • C, whereas a green roof reduced temperature fluctuations in the roof membrane to a median of 5-7 • C the entire year. In addition to thermal aspects, there are many other arguments supporting the application of green roofs, terraces and walls on a large scale in urban areas: they counteract climate changes and reduce the emission of CO 2 into the atmosphere, nullify the negative effects of urbanization, reduce smog [15][16][17], retain rainwater and delay runoff [18][19][20][21], suppress noise, create friendly living and leisure space, and improve the aesthetics of buildings [22,23]. In Poland, work is currently in progress on preparing urban adaptation plans for climate change in which green roofs are among the basic adaptation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Both types of intensive gardens require labour-intensive care, regular fertilization, as well as irrigation and drainage systems (Oberndorfer et al, 2007;FLL, 2008). Green roof installation can be benefi cial both at building and urban scale as it can: contribute to energy saving (Takakura, Kitade & Goto, 2000;Theodosiu, 2003;Fang, 2008;Dohojda, Podawca & Witkowska--Dobrev, 2018) decrease thermal oscillations on the rooftop surface that, in turn, can prolong the lifespan of the rooftop membrane (Jelinkova, Dohnal & Picek, 2015) abate noise (Van Renterghem & Botteldooren, 2009), enhance air quality (Yang, Yu & Gong, 2008;Li et al, 2010), contribute to beautifi cation (Oberdorfen et al, 2007), enhance urban biodiversity (Brenneisen, 2006), reduce storm water runoff (Czemiel Berndtsson, 2010;Nawaz, McDonald & Postoyko, 2015;Pęczkowski, Kowalczyk, Szawernoga, Orzepowski, Żmuda & Pokładek, 2018), and mitigate urban heat island (Takebayashi & Moriyama, 2007;Taleghani, Tenpierik, van den Dobbelsteen & Sailor, 2014;Baryła, Gnatowski, Karczmarczyk & Szatyłowicz, 2019). Simultaneously, the aforementioned parameters assume a different importance depending on the environmental conditions (Susca, 2019).…”
Section: Introductionmentioning
confidence: 99%